2006
DOI: 10.1038/sj.jid.5700168
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Independent Activation of the EGFR by Lipid Raft Disruption

Abstract: Normal and immortalized keratinocytes demonstrate large aggregates of lipid rafts, detectable by membrane staining with fluorescently tagged cholera toxin (CTx). As lipid rafts are known to regulate the function of many surface receptors, we wished to investigate their impact on the EGFR in HaCaT cells. When rafts were disrupted by cholesterol sequestration with methyl-beta-cyclodextrin (MbetaCD) or filipin III, EGFR rearranged into approximately micrometer large clusters outside the CTx(bright) raft aggregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
78
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 48 publications
20
78
0
Order By: Relevance
“…In contrast, the late activation remained in cells pretreated with nystatin, suggesting that the late signaling response of ERK1/2 and CaMKII leading to proliferation was indicative of another originating source that was not in lipid raft domains. This has been suggested in research highlighting how EGFR can be susceptible to ligand-free activation and can produce a proliferation response when it has been released to nonlipid raft areas of the cell membrane (56,57). However, it is not known whether this occurs in fibroblasts, in the absence of HA or CD44.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the late activation remained in cells pretreated with nystatin, suggesting that the late signaling response of ERK1/2 and CaMKII leading to proliferation was indicative of another originating source that was not in lipid raft domains. This has been suggested in research highlighting how EGFR can be susceptible to ligand-free activation and can produce a proliferation response when it has been released to nonlipid raft areas of the cell membrane (56,57). However, it is not known whether this occurs in fibroblasts, in the absence of HA or CD44.…”
Section: Discussionmentioning
confidence: 99%
“…For these experiments we used the polyene antibiotic nystatin, which sequesters free cholesterol without considerable extraction of this sterol . Since another cholesterol-extracting agent, methyl-β-cyclodextrin, has previously been found to stimulate EGFR activity, we checked the effect of nystatin on several cellular functions (Lambert et al, 2006;Ringerike et al, 2002). These control experiments showed that nystatin treatment did not affect EGFR activity, cell shape, or the distribution of GM1, GPI-GFP or EGFR (supplementary material Figs S3 and S4).…”
Section: Nanoscale Colocalization Of Gm1 With Egfr Is Cholesterol Indmentioning
confidence: 99%
“…Furthermore, cholesterol may play a crucial role in modulating signaling from plasma membrane-associated receptors. Thus, the cholesterol-depleting agent methyl h-cyclodextrin (MhCD) can cause ligand-independent activation of the EGFR, apparently by altering membrane lipid organization (11)(12)(13)24). By contrast, depletion of cholesterol from vascular smooth muscle cells by treatment with MhCD led to inhibition of angiotensin IIstimulated phosphorylation of the EGFR (25), and treatment of prostate cancer cells with MhCD to reduce cellular cholesterol levels inhibited phosphorylation of EGFR and the downstream protein AKT (10).…”
Section: Introductionmentioning
confidence: 99%